Evaluation of visual ergonomics in microsurgery: a real-time video processing solution - Mukash, Gaukhar; Vartianen, Paavo; Torkamani-Azar, Mastaneh; Karadis, Zeynel; Faraz, Mehdi; Bednarik, Roman; Karjalainen, Pasi A.; Iso-Mustajärvi, Matti; Hussein, Ahmed (Springer Science and Business Media LLC, 2026)
Purpose: Surgeons' visual and ergonomical challenges are long-standing concerns since the use of microscopes in surgical procedures. Although devices have been improved in the last few decades, the problem of narrow visual fields in high magnification surgeries persists. This study aims to identify the visual ergonomics challenges among microsurgeons and assess the need for novel assistive surgical solutions.
Methods: The study consisted of two parts: a survey and a hands-on experiment. Sixteen surgeons from neurosurgery and otolaryngology (ENT) specialties were invited to semi-structured interviews on challenges encountered when using surgical microscopes and evaluation of the two proposed technological solutions: CPM (context-preserving magnification) and IT (instrument transparency). Following a demonstration of these software solutions, a survey utilizing a Likert scale was administered. The second part of the study involved twelve practicing neurosurgeons who performed a task using a novel solution and compared it to a standard operative microscope setting.
Results: The most common challenges reported were visual obstruction of field by instruments (93.75%), blurring of structures and light reflection (81.25%), and loss of context (68.75%). 50% of surgeons agreed that adjusting zoom and focus takes a considerable amount of time from surgery and 56% stated that they had at least one episode of difficulty seeing depth. Notably, 69% of respondents expressed interest in testing prototypes of both proposed solutions in real surgery, with a particular preference for instrument transparency. Furthermore, the context-preserving magnification solution hands-on trial demonstrated a 40% reduction in task completion time for 60% of participants. However, one participant found no advantage, and others took longer to complete tasks with the solution compared to standard settings.
Conclusion: Our solution addresses the top visual challenges and instrument obstruction remains a top challenge in high magnification microsurgery. We showed that surgeons are highly likely to use novel assistive technologies that provide wider visual field and transparent instruments.
Keywords: Image-guided surgery; Instrument transparency; Microsurgery; Minimally invasive surgery; Surgical microscope.